Global marketing : a decision-oriented approach. - Hollensen, Svend, ....- (Harlow : Prentice Hall, 2010)
The globalization of companies is the involvement of customers, producers, suppliers, and other stakeholders in the global marketing process. Global marketing therefore reflects the trend of firms selling products and services across many countries around the world. Drawing on an incomparable breadth of international examples, Svend Hollensen not only demonstrates how global marketing works, but also how it relates to real decisions around the world.
Keywords: Go international; International office; Marketing